Structure of aqueous electrolyte solutions near a hydrophobic surface - Kinoshita, M. (Condensed Matter Physics, 2007)
The structure of aqueous solutions of 1:1 salts (KCl, NaCl, KF, and CsI) near a hydrophobic surface is analysed using the angle-dependent integral equation theory. Water molecules are taken to be hard spheres imbedded with multipolar moments including terms up to octupole order, and hard spherical ions are immersed in this model water. The many-body interactions associated with molecular polarizability are treated at the self-consistent mean field level. The effects of cationic and anionic sizes and salt concentration in the bulk are discussed in detail. As the salt concentration increases, the layer of water molecules next to the surface becomes denser but its orientational order remains almost unchanged. The concentration of each ion at the surface can be drastically different from that in the bulk. As a striking example, at sufficiently low salt concentrations, the concentration of I⁻ is about 500 times higher than that of F⁻ at the surface.